2019
DOI: 10.1503/cjs.009217
|View full text |Cite
|
Sign up to set email alerts
|

Relation between socioeconomic variables and surgical, systemic and radiation treatment in a cohort of patients with breast cancer in an urban Canadian centre

Abstract: Background: Studies have shown an association between socioeconomic status and breast cancer treatment. We examined the relation between socioeconomic status and the treatment of breast cancer (surgical, systemic and radiation) in a universal health care system. Method: Data from a single urban Canadian centre were collected for consecutive patients who received a diagnosis of breast cancer from January 2010 to December 2011. Variables included patient and disease factors, surgery type, systemic and radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…We screened the titles and abstracts of 806 unique articles, assessed the full text of 70 articles, and found twelve articles that met all inclusion criteria for qualitative synthesis. [18][19][20][21][22][23][24][25][26][27][28][29] The selected articles ranged in publication date from 1997 to 2020 with data collected from 1970 to 2017. Three articles reported on data collected in the United States, three in China, and one each in Canada, United Kingdom, Denmark, Italy, Sweden, and Pakistan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened the titles and abstracts of 806 unique articles, assessed the full text of 70 articles, and found twelve articles that met all inclusion criteria for qualitative synthesis. [18][19][20][21][22][23][24][25][26][27][28][29] The selected articles ranged in publication date from 1997 to 2020 with data collected from 1970 to 2017. Three articles reported on data collected in the United States, three in China, and one each in Canada, United Kingdom, Denmark, Italy, Sweden, and Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…24 Two out of seven articles showed no relationship between education level and rates of BCS. 22,25 In articles that collected patients' incomes, most often self-reported, five out of seven showed that rates of BCS were lower (compared to mastectomy) among patients with lower income. 20,24,26,27,29 Two articles showed no relationship between income level and rates of BCS.…”
mentioning
confidence: 99%
“…Some significant factors that affected this conclusion were employment, education, and the number of radiation oncologists in the areas examined. All significant variables were directly correlated with lower levels in rural areas creating a disparity [ 15 ]. Viewing things from a larger perspective, when examining breast cancer worldwide, a significant distinction was shown between urban and rural populations.…”
Section: Reviewmentioning
confidence: 99%
“…An AI algorithm may flag a possibly questionable medical decision, acting as a needed check point. For example, a Canada-based study showed that when caring for breast cancer patients, employment status consistently predicted the use of systemic and radiation treatment [39]. Another study from Sweden showed that socioeconomic status differs between breast cancer patients treated with mastectomy and breast conservation, even in a national healthcare system that is expected to offer all women the same standard of care [40].…”
Section: Using Ai As a Tool To Combat Unconscious Bias In Medicinementioning
confidence: 99%